Improving the behavior of the CBF system using an innovative box section damper: Experimental and numerical study - Ghadami, Abbas; Ghamari, Ali; Putra Jaya, Ramadhansyah (Institution of Structural Engineers, 2024)
In this study, an innovative shear damper made of a box section with an easily constructed method, lower cost, and higher energy dissipation capacity compared to existing dampers was introduced to address the low energy dissipation capacity of Concentrically Braced Frames (CBFs) resulting from the buckling of their diagonal compression members under earthquake loading. In this regard, firstly, an experimental test was conducted to evaluate the cyclic performance of the proposed damper. Subsequently, a comprehensive parametric study, based on robust finite element analysis validated by experimental results, was carried out to examine the effects of the proposed passive metallic energy damper on the cyclic performance of CBFs. Experimental and numerical results indicated that the proposed damper exhibits suitable performance with stable hysteresis curves and no degradation in stiffness, strength, and energy dissipation. The results also revealed that the proposed damper demonstrates an overstrength exceeding 1.5 (as recommended by AISC341), and therefore, an overstrength of 2.0 was proposed for the damper. Furthermore, limitations of ρ > 0.55 and ψ > 10 must be applied in the damper design, where…. For optimal performance, it is suggested to design the damper in a way that its web slenderness varies between 67 and 113. Additionally, the proposed equation was in good agreement with finite element results in predicting the ultimate strength of the damper.